中央ドロンイングモードランド地学調査隊報告2015-2016（JARE-57） - 菅沼, 悠介; スガヌマ, ユウスケ; 金田, 平太郎; カネダ, ヘイタロウ; 小山, 拓志; コヤマ, タクシ; 外田, 智千; ホカダ, トモカズ; 赤田, 幸久; アカダ, ユキヒサ; Suganuma, Yusuke; Kaneda, Heitaro; et al. (国立極地研究所, 2016)
第57次日本南極地域観測隊（JARE-57）夏隊の一部は，2015-2016の夏期に，中央ドロンイングモードランドにおいて氷河地形・地質調査を実施した．本調査隊のメンバー構成は，地形調査担当3名，地質調査担当1名，およびフィールドアシスタント（FA）1名である．本調査はNorwegian Polar Institute（NPI）とSouth African National Antarctic Program（SANAP）の協力のもとに，日本の観測隊として初めてNPI の大陸間フライトを利用し，Troll 基地およびSANAE 基地を拠点とした調査を実施した．大陸間フライトは，ドイツ（復路はノルウェー）から南アフリカのケープタウンを経由して，Troll 基地に到達した．また，SANAE 基地のヘリコプターを用いて，ドロンイングモードランドの山々やヌナタックでの調査を実施した．本稿では調査，設営，気象をはじめとする本調査隊の行動全般について報告する． Geomorphologic and geologic field surveys were conducted in central Dronning Maud Land during the summer of 2015-2016 as part of the 57th Japanese Antarctic Research Expedition (JARE-57). The members of the field expedition included three geomorphologists, a geologist, and a field assistant. This field expedition was fully supported by the Norwegian Polar Institute (NPI) and the South African National Antarctic Program (SANAP), and it was the first JARE expedition to use the Troll and SANAE stations. The NPI provided airborne access from Germany (Norway, on the way back) to the Troll station in central Dronning Maud Land via Cape Town, South Africa. The SANAP provided a helicopter to access nunataks and mountains in this area from the Troll and SANAE stations. This report summarizes the activities of this field expedition including fieldwork, logistics, and weather observations. departmental bulletin paper